2019
DOI: 10.5194/bg-2019-29
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of nitrogen deposition on growing-season soil methane sink across global forest biomes

Abstract: <p><strong>Abstract.</strong> Anthropogenic alteration of global nitrogen (N) deposition has resulted in profound impacts on soil fluxes of greenhouse gases in terrestrial ecosystems. However, the response of soil methane (CH<sub>4</sub>) flux to N deposition remains poorly quantified in global forest. Based on a synthesis of experimental results from literature, we evaluated the effects of N deposition on growing-season soil CH4 flux across forest biomes. A distinction was made b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Application of inorganic fertilizer may have enhanced CH 4 oxidation, similar to Nyamadzawo et al (2014) who noted that N application to sandy loam soils reduced CH 4 emissions. When N is applied as inorganic fertilizer in N-deficient conditions (Du et al, 2019), it relieves the N limitation of cell growth and subsequently increases the activity of methanotrophic microorganisms in the long term, increasing CH 4 uptake (Bodelier et al, 2000). Nitrogen application (either as ammonium or nitrate) also promotes the growth and activity of the nitrifying population, co-oxidizing atmospheric CH 4 thus increasing CH 4 uptake (Bodelier & Laanbroek, 2004;Reay et al, 2005).…”
Section: Journal Of Geophysical Research: Biogeosciencesmentioning
confidence: 99%
“…Application of inorganic fertilizer may have enhanced CH 4 oxidation, similar to Nyamadzawo et al (2014) who noted that N application to sandy loam soils reduced CH 4 emissions. When N is applied as inorganic fertilizer in N-deficient conditions (Du et al, 2019), it relieves the N limitation of cell growth and subsequently increases the activity of methanotrophic microorganisms in the long term, increasing CH 4 uptake (Bodelier et al, 2000). Nitrogen application (either as ammonium or nitrate) also promotes the growth and activity of the nitrifying population, co-oxidizing atmospheric CH 4 thus increasing CH 4 uptake (Bodelier & Laanbroek, 2004;Reay et al, 2005).…”
Section: Journal Of Geophysical Research: Biogeosciencesmentioning
confidence: 99%
“…Although ammonia (NH 3 ) neutralizes acidity in rainwater due to the formation of ammonium (NH 4 + ), significant acidification occurs in the soil due to NH 4 + assimilation and nitrification (Liu et al, 2019;van Breemen et al, 1983). Globally, Europe, North America, and subsequently East Asia (particularly southern China) were the three largest acid rain regions, of major environmental concern (Duan et al, 2016). Acid deposition has the potential to erode artifacts and building materials directly, as well as damage crops and trees.…”
Section: H I G H L I G H T S G R a P H I C Abstractmentioning
confidence: 99%
“…Acid deposition has the potential to erode artifacts and building materials directly, as well as damage crops and trees. In terrestrial ecosystems, it can indirectly lead to acidification and eutrophication of soil and surface water, as well as to the release of nitrous oxide (N 2 O) (Duan et al, 2016). N 2 O is a potent greenhouse gas with a long residence time in the troposphere, while also contributing to the destruction of stratospheric ozone (Ravishankara et al, 2009).…”
Section: H I G H L I G H T S G R a P H I C Abstractmentioning
confidence: 99%
“…Notably, there are varying results on how N addition affects CH4 uptake from tropical forest soils. For instance, Veldkamp et al (2013) found no effect of N on CH4 uptake while Du et al (2019) measured reduced CH4 consumption following addition of N to a tropical forest, with the latter study suggesting an inhibitory effect of N on CH4 uptake (Bodelier and Steenbergh, 2014;Seghers et al, 2003;Zhang et al, 2011). Aronson and Helliker (2010) argue that the observed differences in the 65 measured CH4 fluxes in the two separate studies were likely due to the different amounts of N added in the respective experimental setups.…”
mentioning
confidence: 94%